Study of plasma fibrinogen in cases with hypertriglyceridemia - Aziz, Rehana; Haque, Mahmudul; Chowdhury, Md Sirajul Islam; Ghose, Sankar Kumar; Taher, MA; Sultan, Md Tipu (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3846 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):17-19